Dukungan Sosial Terhadap Motivasi Anak Yatim Dalam Menghadapi Tantangan Hidup Di Panti Asuhan Mamiyai - Cinta Mollyka Rambe; Efi Brata Madya (Ganaya : Jurnal Ilmu Sosial dan Humaniora, 2025)
This study investigates the forms of social support received by orphans at Mamiyai Orphanage and examines how such support influences their motivation to face life’s challenges. Using a descriptive qualitative approach, data were collected through in-depth interviews, participatory observations, and triangulation to ensure validity. The findings indicate that social support from caregivers, peers, and the community plays a crucial role in enhancing the motivation of orphans. Emotional support expressed through affection and attention, alongside material assistance, provides a sense of security and fosters mental resilience. Furthermore, warm interactions within the orphanage environment and with the surrounding community strengthen their capacity to adapt to various pressures. Despite existing challenges that may hinder optimal support, the study highlights the importance of continuous collaboration between orphanages, society, and relevant stakeholders. Strengthened social support is essential not only for motivating orphans but also for promoting their overall psychological development and preparing them for a better future.